2004
DOI: 10.1111/j.1440-1827.2004.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between morphology and angiogenesis in human early colorectal cancers

Abstract: Morphologically, early colorectal cancers are divided into two types: polypoid cancers and non-polypoid cancers. They vary in growth pattern, progression, and genetic alteration. Angiogenesis between polypoid and non-polypoid cancers may also be different. Therefore, the present study aims to evaluate angiogenesis in the early stages of colorectal malignancy, with particular attention to the morphological differences. The serial slides of all materials (48 polypoid cancers, 10 non-polypoid cancers, 20 adenomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The volume of a polypoid lesion is approximately twice that of a nonpolypoid with the same diameter, and the interstitial space available for immune / epithelial cell interaction is thus much larger. Early-stage polypoid colorectal cancers have more extensive microvascular networks than their nonpolypoid counterparts [ 46 ]. A similar difference might exist in precancerous lesions, and this facilitate the immune cells’ infiltration of the stroma of polypoid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of a polypoid lesion is approximately twice that of a nonpolypoid with the same diameter, and the interstitial space available for immune / epithelial cell interaction is thus much larger. Early-stage polypoid colorectal cancers have more extensive microvascular networks than their nonpolypoid counterparts [ 46 ]. A similar difference might exist in precancerous lesions, and this facilitate the immune cells’ infiltration of the stroma of polypoid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…4). CD105 is expressed in vascular endothelial cells of polypoid-type early colon cancer [20]. To our knowledge, the present study is the first to identify CD105 expression at levels corresponding to the depth of cancer invasion in the colon adenoma-carcinoma sequence (adenoma, carcinoma in adenoma, adenocarcinoma, and lymph node metastasis).…”
Section: Discussionmentioning
confidence: 99%
“…CD105 is emerging as a prime vascular target of antiangiogenetic cancer therapy [10]. We reported that the predominantly CD105-positive microvessel count of polyploid-type early colon cancer is higher than that of nonpolyploid-type early cancer [20]. However, to our knowledge, the expression of CD105 in vessels of lesions invading all the various tissue layers during the colon adenoma-carcinoma sequence (adenoma, carcinoma in adenoma, and adenocarcinoma) has not been compared with that of other endothelial markers.…”
Section: Introductionmentioning
confidence: 98%
“…CD105 is predominantly expressed on cellular lineages within the vascular system and is overexpressed on proliferating endothelial cells. Therefore, CD105 is considered to be a powerful marker of neovascularization [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%